Wpływ czynników wewnętrznych na strukturę systemu budżetowania - Fjałkowska, Danuta (The Influence of Internal Factors on the Structure of the Budgeting System., 2006)
Mechanisms contained in budgeting can be recognized as a basic set of tools supporting the current organization management, able to cooriginate conditions necessary for shaping the most profitable development of the organization. The first part of this paper contains examples of obligatory as well as individual criteria determining in each organization an internal project space of such a system. In the second part a practical example of a functioning budgeting system has been presented in which the characteristic features and current working conditions of the enterprise have been fully and successfully discussed.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1101, s. 97-107